(untitled) (TAMADDUN NURI JURNALI, 2025)
This article reflects the essence and philosophical features of the neighborhood work system in New Uzbekistan. In our country, mechanisms are being developed to ensure the effective functioning of the “Mahallabay” system in practice. Today, republican, regional and district (city) councils are being introduced for the development and support of neighborhoods.